1992
DOI: 10.1200/jco.1992.10.5.795
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin neurotoxicity: the relationship between dosage, time, and platinum concentration in neurologic tissues, and morphologic evidence of toxicity.

Abstract: The dorsal root ganglia was the most vulnerable neural structure. This is consistent with the clinical presentation of sensory neuropathy in cisplatin neurotoxicity. Central structures of the spinal cord and brain were protected from platinum accumulation. The increasing histopathologic toxicity, with an index of exposure to platinum, suggests that it is retained indefinitely in an actively neurotoxic form. The pharmacologic parameters examined correlate with the development of and are consistent with the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
189
0
7

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(207 citation statements)
references
References 25 publications
9
189
0
7
Order By: Relevance
“…It may be that the elimination half-life of platinum in neural tissue is less than 12 days and that steady-state concentrations had already been reached before 8 weeks. Gregg et al (1992), studied platinum concentrations in neurological tissue taken after death from cisplatin-treated humans and described a relationship between the tissue accumulation of platinum and peripheral neurotoxicity (Gregg et al, 1992). As in our study, they found preferential distribution of platinum to peripheral vs central nervous tissues, but tissue levels were two-to fourfold higher than in our rats even though we used more toxic platinum derivatives.…”
Section: Discussionmentioning
confidence: 44%
“…It may be that the elimination half-life of platinum in neural tissue is less than 12 days and that steady-state concentrations had already been reached before 8 weeks. Gregg et al (1992), studied platinum concentrations in neurological tissue taken after death from cisplatin-treated humans and described a relationship between the tissue accumulation of platinum and peripheral neurotoxicity (Gregg et al, 1992). As in our study, they found preferential distribution of platinum to peripheral vs central nervous tissues, but tissue levels were two-to fourfold higher than in our rats even though we used more toxic platinum derivatives.…”
Section: Discussionmentioning
confidence: 44%
“…The main neuropathy of CDDP is sensory peripheral neuropathy (van der Hoop et al, 1990;Gregg et al, 1992). A delay in SNCV due to the injury of dorsal root ganglia and peripheral nerve has previously been reported in rats given CDDP, although MNCV was preserved in the tail and hind paws of rats (McKeage et al, 1994;Tredici et al, 1998;Meijer et al, 1999;Tredici et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…11 At least in some of these manifestations, there is an association with the finding of high levels of tissue platinum in the brain. 12 Chemotherapy-induced cerebral abnormalities occur in a wide variety of settings and present with a wide range of clinical findings. Neurologic complications have been described with antineoplastic drugs including alkylating agents, antimetabolites, periwinkle derivatives and other agents including cisplatin and L-asparaginase.…”
Section: Discussionmentioning
confidence: 99%